Przerywanie ciąży – rozważania w świetle orzeczenia Trybunału Konstytucyjnego w sprawie K 1/20 - Szudejko, Piotr (Studia Prawa Publicznego, 2022)
The article presents the issues of legal regulation of termination of pregnancy in the context of the jurisprudence of the Constitutional Court (CC), in particular the ruling in the case K 1/20. The discussion opens with an analysis of models of abortion practices regulations, as well as the solutions adopted in the Polish legal system, with a short historical introduction. It is emphasized how important is the issue, which results from the fundamental differences in worldviews between the supporters and opponents of the permissibility of the practice of termination of pregnancy, which is expressed in the name given to this medical practice. The right to life as an element of the human rights system is discussed, both in terms of international law and the provisions of the Polish constitution. Next, the Polish provisions on the admissibility of termination of pregnancy are presented along with a historical outline, with particular emphasis on the ruling in the case K 26/96. Based on the above discussion, the resolution in the case K 1/20 was discussed, in which the CC found the so-called embryopathological premise for termination of pregnancy to be incompatible with Polish Constitution. A polemic with the justiﬁcation of the decision is presented, including the errors of interpreta-tion committed by the CC with regard to the constitutional and international form of the right to the protection of life. It is indicated that in the Polish legal system only the right to protection of life exists, not the right to life, which is referred to both by the CC and most of the doctrine. Despite the fact that this resolution does not remove the norm from the legal system, the author draws attention to the practical consequences of issuing it, in particular the occurrence of the so-called ‘chilling effect’ and unjustiﬁed activity of the law enforcement authorities. The ﬁnal part of the article presents conclusions on how to legally regulate the termination of pregnancy.